2011
DOI: 10.1371/journal.pone.0024126
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil Impairs Memory in Healthy Older Subjects: Behavioural, EEG and Simultaneous EEG/fMRI Biomarkers

Abstract: Rising life expectancies coupled with an increasing awareness of age-related cognitive decline have led to the unwarranted use of psychopharmaceuticals, including acetylcholinesterase inhibitors (AChEIs), by significant numbers of healthy older individuals. This trend has developed despite very limited data regarding the effectiveness of such drugs on non-clinical groups and recent work indicates that AChEIs can have negative cognitive effects in healthy populations. For the first time, we use a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…Consistently, we found abnormal connectivity measures in the delta band in both BD and ADHD. Nevertheless, other bands such as beta [48] should also be assessed in future studies of the DMN in BD and ADHD. …”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found abnormal connectivity measures in the delta band in both BD and ADHD. Nevertheless, other bands such as beta [48] should also be assessed in future studies of the DMN in BD and ADHD. …”
Section: Discussionmentioning
confidence: 99%
“…Another potential approach to be used within a PM paradigm is to measure the effects of a single dose [279282] and investigate the predictive power of the single dose over the effectiveness of the therapeutic strategy for the biomarkers-characterized patient. The single dose approach has the potential to inform the tailoring of the therapeutic intervention by providing information about potential medium to long term effects of any treatment.…”
Section: Contribution and Role Of Functional Magnetic Resonance Imagimentioning
confidence: 99%
“…Three of these were in elderly subjects, one of these concerned subjects with Mild Cognitive Impairment. Three studies reported improved episodic memory performance (Gron et al 2006(Gron et al , 2005Stough et al 2009), whereas one reported impaired episodic memory performance (Balsters et al 2011). The latter was in healthy elderly subjects and the only clear factor in which this study was different than the other three reporting positive effects of cholinesterase inhibitors was that Balsters et al were using PAL, a nonverbal episodic memory task, whereas the other studies were using Word List tests.…”
Section: Acetylcholinementioning
confidence: 71%